2022
DOI: 10.1001/jamanetworkopen.2022.30243
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of National Medical Societies’ Accessible Resources to Support Underrepresented Minority and Female Trainees

Abstract: IMPORTANCEThe lack of racial, ethnic, and gender diversity in medicine has been recognized as problematic, but the question of what medical educators and societies are doing to rectify and promote representation of historically marginalized groups persists. OBJECTIVE To examine what easily accessible resources are offered by medical and surgical societies to support women and individuals in minority groups that are underrepresented in medicine (URiM). DESIGN, SETTING, AND PARTICIPANTS This cross-sectional stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 23 publications
(38 reference statements)
0
2
0
Order By: Relevance
“…The median conference fee for students in the member category was 191.55 USD 16), and 950.04 USD (787.41-1237.46), respectively. Similarly, the median conference fee price for non-member residents, fellows, and staff was 49.9%, 54.9%, and 49.9% greater than that for member trainees of the same category, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The median conference fee for students in the member category was 191.55 USD 16), and 950.04 USD (787.41-1237.46), respectively. Similarly, the median conference fee price for non-member residents, fellows, and staff was 49.9%, 54.9%, and 49.9% greater than that for member trainees of the same category, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Despite certain residency training programs and surgical societies offering financial compensation to trainees wishing to participate in surgical conferences, these financial stipends are likely to only cover a proportion of the total associated costs and selectively benefit individuals from better‐funded academic institutions, once again sidelining trainees from minority groups, smaller institutions, and LMICs where funding is often lacking. Furthermore, in another recent study evaluating 45 medical and surgical societies, only 15 (33%) offered scholarships directed toward individuals from minority groups that are underrepresented in medicine despite 84.4% of these societies having easily accessible published diversity statements [16]. Although we have seen improvements with certain financial resources being offered to trainees wishing to participate in surgical education, many of these opportunities may also be limited to specific levels of training, such as for trainees who are already residents or fellows in their desired field of practice.…”
Section: Discussionmentioning
confidence: 99%
“…Plastic surgery programs are working to mitigate the costs of away rotations by offering to visit student scholarships, though these efforts are still relatively few in comparison to the number of students who wish to participate in away rotation opportunities. 23 Recent studies show that positive relationships with role models have been associated with students going into their associated specialty areas, with internal medicine, family medicine, and pediatrics identified as the most frequent residency match choices when coupled with the presence of a mentor. 24,25 A 2019 survey of the American Society of Plastic Surgeons members found that although 94.05% of plastic surgeons believe mentorship is valuable, only 15.16% reported a structured mentorship program, with fewer mentorship opportunities for women, underrepresented minorities, and junior plastic surgeons, subsequently resulting in lower job satisfaction.…”
Section: Discussionmentioning
confidence: 99%
“…This cost is compounded for students who pursue numerous away rotations or sub-internships and serves as a significant burden. Plastic surgery programs are working to mitigate the costs of away rotations by offering to visit student scholarships, though these efforts are still relatively few in comparison to the number of students who wish to participate in away rotation opportunities 23 …”
Section: Discussionmentioning
confidence: 99%